A full-silicon flame-retardant cross-linked gel electrolyte, a preparation method and application thereof
Patent Information
- Application Number
- CN202611159998.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-03
AI Technical Summary
[0005]本发明的目的是为了解决现有凝胶电解质阻燃性能不足、热稳定性较差、易发生电解液泄漏以及电化学稳定性不足的问题,提供一种全含硅阻燃交联凝胶电解质及其制备方法和应用
本发明实施例提供的全含硅阻燃交联凝胶电解质,将含乙烯基硅氧基的磷酸酯衍生物与含硅双键可聚合单体共同引入硅基电解液中,经引发聚合反应后,能够在电池内部原位形成稳定的三维交联凝胶网络。该凝胶网络能够有效固定硅基电解液,降低电解液泄漏风险,同时将含硅含磷阻燃结构单元固定在凝胶骨架中,使所得凝胶电解质具有良好的阻燃性能、热稳定性和电化学稳定性。
Smart Images

Figure CN122677527B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery electrolyte technology, specifically to a fully silicon-containing flame-retardant crosslinked gel electrolyte, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and high operating voltage, have been widely used in electric vehicles, portable electronic devices, and energy storage systems. However, as battery energy density continues to increase, the safety of the electrolyte becomes increasingly prominent. Traditional liquid electrolytes are typically composed of organic solvents such as carbonates and ethers with lithium salts. These solvents generally suffer from defects such as volatility, leakage, and flammability. When batteries are subjected to abuse conditions such as compression, puncture, overcharging, short circuits, or high-temperature shocks, liquid electrolytes are prone to combustion or even thermal runaway, seriously affecting the safe use of the battery. Therefore, improving the flame retardant properties and thermal stability of the electrolyte is an important direction for the development of high-safety lithium batteries.
[0003] To address these issues, solid-state electrolytes and gel electrolytes have attracted widespread attention. While solid-state electrolytes can reduce flammable liquid components, they suffer from low room-temperature ionic conductivity and poor interfacial contact with electrodes, easily leading to increased interfacial impedance and decreased rate performance. Gel electrolytes, by immobilizing or adsorbing liquid electrolytes through a polymer network, can combine high ionic conductivity with a certain degree of morphological stability and reduce the risk of electrolyte leakage to some extent. However, existing gel electrolytes mostly use common organic polymers as their framework, and their intrinsic flame retardancy and thermal stability are still insufficient. Under high-temperature or open-flame conditions, they may still soften, decompose, or burn, making it difficult to meet the application requirements of high-safety batteries.
[0004] Existing flame-retardant gel electrolytes typically rely on the addition of external flame-retardant additives or the introduction of flame-retardant structural units to achieve their flame-retardant function. However, small-molecule flame-retardant additives are prone to migration, consumption, or participation in side reactions during long-term cycling, making it difficult to maintain their flame-retardant effect. Furthermore, some flame-retardant polymer gels suffer from problems such as reduced ionic conductivity, increased interfacial impedance, and insufficient electrochemical stability. Therefore, there is an urgent need to develop a novel gel electrolyte that combines flame retardancy, gelation stability, and good ionic conductivity. Summary of the Invention
[0005] The purpose of this invention is to address the problems of insufficient flame retardancy, poor thermal stability, easy electrolyte leakage, and insufficient electrochemical stability of existing gel electrolytes, and to provide a fully silicon-containing flame retardant crosslinked gel electrolyte, its preparation method, and its application.
[0006] In a first aspect, the present invention provides a fully silicon-containing flame-retardant crosslinked gel electrolyte, wherein the fully silicon-containing flame-retardant crosslinked gel electrolyte is obtained by in-situ polymerization of a gel electrolyte precursor solution composed of a silicon-based electrolyte, a phosphate ester derivative containing vinylsiloxy groups, a polymerizable monomer containing silicon double bonds, and an initiator; wherein, The silicon-based electrolyte includes an organosilane solvent, a lithium salt, and functional additives; The phosphate ester derivative containing vinylsiloxy groups contains PO-Si bonds and polymerizable carbon-carbon double bonds in its molecule. The polymerizable monomer containing silicon double bonds contains Si-O bonds and / or Si-C bonds, and also contains polymerizable carbon-carbon double bonds. The phosphate derivative containing vinylsiloxy groups can undergo free radical copolymerization with the polymerizable monomer containing silicon double bonds.
[0007] Furthermore, based on a total mass of 100wt% for the gel electrolyte precursor solution, the mass of the vinylsiloxy phosphate derivative is 2wt%-8wt%, and the molar ratio of the polymerizable carbon-carbon double bond in the vinylsiloxy phosphate derivative and the polymerizable monomer containing silicon double bonds is 1:(0.3-2).
[0008] Furthermore, the silicon-based electrolyte contains, by weight: 65-90 parts of organosilane solvent, 10-30 parts of lithium salt, and 2-8 parts of functional additives.
[0009] Furthermore, in the silicon-based electrolyte, The organosilane solvent is selected from one or more of methyltrimethoxysilane, methoxytrimethylsilane, and methyltris(trimethylsiloxy)silane; The lithium salt is LiFSI and / or LiTFSI; The functional additive is selected from one or more of lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorophosphate, vinylene carbonate, fluoroethylene carbonate, and lithium nitrate.
[0010] Furthermore, the phosphate derivative containing vinylsiloxy groups is tris(vinyldimethylsilyl)phosphate; Furthermore, the silicon-containing double-bond polymerizable monomer is selected from one or more of the following: [dimethoxy(methyl)silyl]methyl methacrylate, bis[3-(methacryloyloxy)propyl]tetramethyldisiloxane, 3-methacryloyloxypropyltrimethoxysilane, methacryloyloxypropyltriethoxysilane, acryloyloxytriisopropylsilane, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, and octavinyl POSS.
[0011] Further, the initiator is selected from thermal initiators or photoinitiators, and the amount of the initiator is 0.2wt%~0.5wt% of the combined mass of the vinylsiloxy phosphate derivative and the silicon double-bond polymerizable monomer; wherein, The thermal initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide and di-tert-butyl peroxide; The photoinitiator is selected from at least one of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned all-silicon-containing flame-retardant crosslinked gel electrolyte, comprising: The silicon-based electrolyte, the vinylsiloxy phosphate derivative, the silicon double bond polymerizable monomer, and the initiator are mixed evenly to obtain a gel electrolyte precursor solution. The gel electrolyte precursor solution is subjected to thermally initiated polymerization or photoinitiated polymerization to obtain the fully silicon-containing flame-retardant crosslinked gel electrolyte.
[0013] Furthermore, the temperature of the thermally initiated polymerization reaction is 40℃-90℃, and the time is 0.5h-12h; the photoinitiated polymerization reaction is carried out by irradiation with ultraviolet light or visible light with a wavelength of 365nm-405nm, and the irradiation time is 1min-60min.
[0014] A third aspect of the present invention provides a lithium battery comprising a positive electrode, a negative electrode, a separator, and the aforementioned all-silicon flame-retardant crosslinked gel electrolyte; wherein the positive electrode active material is selected from LiCoO2 and LiNi. x Co Mn 1-x- O2, LiNi x Co Al 1-x- At least one of O2, LiNi0.8Co0.1Mn0.1O2, LiNi0.6Co0.2Mn0.2O2, LiFePO4, LiMn2O4, and LiNi0.5Mn1.5O4; the negative electrode is selected from one of lithium metal negative electrode, graphite negative electrode, silicon-carbon negative electrode, hard carbon negative electrode, and lithium titanate negative electrode.
[0015] A fourth aspect of the present invention provides the application of the above-described all-silicon flame-retardant crosslinked gel electrolyte in lithium-ion batteries or lithium metal batteries.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: The fully silicon-containing flame-retardant crosslinked gel electrolyte provided in this invention introduces a vinylsiloxy phosphate derivative and a silicon-containing double-bond polymerizable monomer into a silicon-based electrolyte. After initiation of a polymerization reaction, a stable three-dimensional crosslinked gel network can be formed in situ inside the battery. This gel network can effectively fix the silicon-based electrolyte, reducing the risk of electrolyte leakage. At the same time, the silicon- and phosphorus-containing flame-retardant structural units are fixed in the gel framework, giving the resulting gel electrolyte good flame-retardant properties, thermal stability, and electrochemical stability. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in the embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings.
[0018] Figure 1 This is a comparison of the cycle performance of NCM811 / Li batteries provided in Examples 1-8 and Comparative Examples 1-6 of the present invention.
[0019] Figure 2 The FTIR spectra are of TVDMSP monomer, BA monomer, Comparative Example 4 gel and Example 1 gel. Detailed Implementation
[0020] To better understand the above technical solutions, the technical solutions of the embodiments of this application will be described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the embodiments of this application and the specific features in the embodiments are detailed descriptions of the technical solutions of the embodiments of this application, rather than limitations on the technical solutions of this application. In the absence of conflict, the embodiments of this application and the technical features in the embodiments can be combined with each other.
[0021] In a first aspect, this invention provides a fully silicon-containing flame-retardant crosslinked gel electrolyte. The fully silicon-containing flame-retardant crosslinked gel electrolyte is obtained through an in-situ polymerization reaction of a gel electrolyte precursor solution composed of a silicon-based electrolyte, a phosphate ester derivative containing vinylsiloxy groups, a polymerizable monomer containing silicon double bonds, and an initiator; wherein... Silicon-based electrolytes include organosilane solvents, lithium salts, and functional additives; Phosphate ester derivatives containing vinylsiloxy groups contain PO-Si bonds and polymerizable carbon-carbon double bonds in their molecules; The polymerizable monomers containing silicon double bonds contain Si-O bonds and / or Si-C bonds, and also contain polymerizable carbon-carbon double bonds. Phosphate derivatives containing vinylsiloxy groups can undergo free radical copolymerization with the polymerizable monomers containing silicon double bonds.
[0022] The fully silicon-containing flame-retardant crosslinked gel electrolyte provided in this invention introduces a phosphate ester derivative containing vinylsiloxy groups and a polymerizable monomer containing silicon double bonds (an organic monomer derivative containing a polymerizable silicon double bond) into a silicon-based electrolyte. After thermally or photo-initiated polymerization, a stable three-dimensional crosslinked gel network can be formed in situ inside the battery. This gel network can effectively fix the silicon-based electrolyte, reducing the risk of electrolyte leakage, while fixing the silicon- and phosphorus-containing flame-retardant structural units within the gel framework, giving the resulting gel electrolyte excellent flame-retardant properties, thermal stability, and electrochemical stability.
[0023] Specifically, organosilane structures exhibit good thermal stability and interfacial wettability, while phosphorus-containing structures demonstrate typical flame-retardant properties. Phosphate ester derivatives containing vinylsiloxy groups possess PO-Si bonds and polymerizable carbon-carbon double bonds, enabling them to participate in gel network formation as silicon-containing flame-retardant crosslinking agents. By co-constructing in-situ gel electrolytes with silicon-containing polymerizable monomers and silicon-based electrolytes, flame-retardant units are immobilized, reducing electrolyte leakage and combustion risks, and improving battery interfacial stability, safety, and cycle life.
[0024] In this embodiment of the invention, "phosphoester derivatives containing vinylsiloxy groups" refers to phosphate ester compounds containing PO-Si bonds and polymerizable carbon-carbon double bonds in their molecules, having the following general formula: P(=O)(O-SiR¹R²-CH=CH2)3. These compounds can participate in gel network formation as silicon-containing flame-retardant crosslinking agents, and the phosphorus-containing groups and siloxy groups in their structure help improve the flame-retardant properties, thermal stability, and interfacial stability of the electrolyte. Preferably, the vinylsiloxy-containing phosphate derivative is tris(vinyldimethylsilyl)phosphate.
[0025] In this embodiment of the invention, "silicon-containing double-bond polymerizable monomer" refers to an organic monomer compound whose molecule contains Si-O bonds and / or Si-C bonds and polymerizable carbon-carbon double bonds, and which can undergo free radical copolymerization with phosphate ester derivatives containing vinylsiloxane groups. Silicon-containing double-bond polymerizable monomers include, but are not limited to, silicon-containing acrylate derivatives, silicon-containing methacrylate derivatives, vinylsilane derivatives, vinylsiloxane derivatives, silanyl allyl derivatives, silicon nitrile double-bond derivatives, phosphorus-containing silicon double-bond derivatives, and polyvinylsiloxane cage-like derivatives.
[0026] In this embodiment of the invention, "silicon-based electrolyte" refers to an electrolyte system that uses an organosilane solvent as the main solvent or co-solvent and contains lithium salts and functional additives. Silicon-based electrolytes can serve as ion-conducting media while simultaneously improving the flame retardancy, thermal stability, and interfacial wettability of the electrolyte system.
[0027] In some embodiments, based on 100 wt% of the total mass of the gel electrolyte precursor solution, the mass of the vinylsiloxy-containing phosphate ester derivative is 2 wt%-8 wt%, and the molar ratio of the vinylsiloxy-containing phosphate ester derivative to the polymerizable carbon-carbon double bond in the silicon double-bond polymerizable monomer is 1:(0.3-2). Preferably, based on 100 wt% of the total mass of the gel electrolyte precursor solution, the mass of the vinylsiloxy-containing phosphate ester derivative is 3 wt%-5 wt%, and the molar ratio of the vinylsiloxy-containing phosphate ester derivative to the polymerizable double bond in the silicon double-bond polymerizable monomer is 1:(0.8-1.5).
[0028] Specifically, by limiting the two types of polymerizable components by the above-mentioned mass percentage and molar ratio of polymerizable double bonds, it is possible to enable phosphate ester derivatives containing vinylsiloxy groups to participate in network construction as phosphorus-containing and silicon-containing flame-retardant crosslinking units, while enabling polymerizable monomers containing silicon double bonds to enter the gel skeleton as flexible segments or silicon-oxygen functional segments, thereby achieving a balance between gel strength, flame retardant effect and ion transport.
[0029] When the amount of phosphate derivatives containing vinylsiloxy groups is less than 2 wt%, the flame-retardant crosslinking units in the system are insufficient, and the integrity of the gel network and the flame-retardant effect are easily reduced. When the amount is higher than 8 wt%, the viscosity of the precursor solution increases, and the network after polymerization becomes too dense, which may lead to increased gel brittleness and hindered ion migration. It is preferable to control it at 3 wt%-5 wt%, and control the molar ratio of polymerizable carbon-carbon double bonds of the two polymerizable components at 1:(0.8-1.5), which is beneficial to the formation of a continuous, uniform and not excessively dense three-dimensional crosslinked network.
[0030] By simultaneously controlling the composition of the silicon-based electrolyte and the ratio of the two types of polymerizable monomers, the free flow and leakage of liquid components can be reduced, and the fixation of the flame-retardant structure in the gel skeleton can be improved. At the same time, it can be avoided that insufficient gelation is caused by too little polymerizable component, or that the electrolyte content decreases, the ionic conductivity decreases and the interfacial impedance increases due to too much polymerizable component.
[0031] In some embodiments, the silicon-based electrolyte contains, by weight: 65-90 parts of organosilane solvent, 10-30 parts of lithium salt, and 2-8 parts of functional additives. The organosilane solvent is selected from one or more of methyltrimethoxysilane (MTMS), methoxytrimethylsilane (METMS), and methyltris(trimethylsiloxy)silane (TTMS). The lithium salt is LiFSI and / or LiTFSI; The functional additives are selected from one or more of lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorophosphate, vinylene carbonate, fluoroethylene carbonate, and lithium nitrate.
[0032] In a preferred embodiment, the silicon-based electrolyte comprises, by weight: 75-80 parts MTMS, 5-10 parts METMS, 15-25 parts LiFSI, 0.4-0.6 parts lithium difluorooxalate borate, and 1.5-2.5 parts vinylene carbonate.
[0033] In a preferred embodiment, the silicon-based electrolyte comprises, by weight: 75-80 parts of METMS, 15-25 parts of LiFSI, 0.4-0.6 parts of lithium difluorooxalate borate, and 1.5-2.5 parts of vinylene carbonate.
[0034] In a preferred embodiment, the silicon-based electrolyte comprises, by weight: 70-80 parts TTMS, 15-25 parts LiFSI, 0.4-0.6 parts lithium difluorooxalate borate, and 1.5-2.5 parts vinylene carbonate.
[0035] Specifically, the aforementioned silicon-based electrolyte, primarily composed of organosilane solvents, can reduce the flammability of traditional carbonate electrolytes and improve the wettability of the electrolyte to the membrane and electrode interfaces. Controlling the organosilane solvent to 65-90 parts helps ensure the system has sufficient silicon-based flame-retardant components and liquid-phase conduction channels; controlling the lithium salt to 10-30 parts helps balance lithium-ion concentration, solution viscosity, and ion migration ability; and controlling the functional additives to 2-8 parts helps promote the formation of a stable SEI / CEI interface film.
[0036] When MTMS is combined with METMS, it can balance solvent flowability, salt solubility, and silicon-based flame retardant properties. A higher METMS content results in lower precursor liquid viscosity, which is beneficial for uniform cell wetting and in-situ polymerization. TTMS has a high siloxane structure content, which helps to further improve thermal stability and hydrophobic flame retardant properties. Combining LiFSI and / or LiTFSI with the above-mentioned silicon-based solvents can reduce the risk of interfacial instability caused by hydrolysis side reactions and acidic byproducts in the LiPF6 system.
[0037] In some embodiments, the vinylsiloxy phosphate derivative is tris(vinyldimethylsilyl)phosphate; the polymerizable monomer containing silicon double bonds is selected from one or more of [dimethoxy(methyl)silyl]methyl methacrylate, bis[3-(methacryloyloxy)propyl]tetramethyldisiloxane, 3-methacryloyloxypropyltrimethoxysilane, methacryloyloxypropyltriethoxysilane, acryloyloxytriisopropylsilane, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, and octavinylPOSS.
[0038] Specifically, the aforementioned polymerizable monomers containing silicon double bonds all contain carbon-carbon double bonds that can participate in free radical polymerization, enabling them to copolymerize or crosslink with tris(vinyldimethylsilyl)phosphate esters, thus fixing the silicon-containing segments and flame-retardant crosslinking units together within the gel backbone. Silicone acrylate or methacrylate monomers exhibit high reactivity, facilitating in-situ gelation under relatively mild conditions; vinylsiloxane monomers can improve network flexibility and interfacial wettability; and POSS-type polyvinyl monomers can provide cage-like silicon-oxygen structures and multi-point crosslinking, which are beneficial for enhancing the thermal, mechanical, and dimensional stability of the gel.
[0039] Compared with ordinary acrylates, methacrylates or ether crosslinkers that do not contain silicon, polymerizable monomers containing silicon double bonds can increase the silicon content in the gel backbone and form a phosphorus-silicon synergistic flame-retardant structure with phosphorus-containing crosslinking units, thereby improving self-extinguishing ability, high-temperature morphological stability and high-voltage interface stability.
[0040] In some embodiments, the initiator is selected from thermal initiators or photoinitiators; the amount of initiator used is 0.2 wt% to 0.5 wt% of the combined mass of the vinylsiloxy phosphate derivative and the silicon double-bond polymerizable monomer; The thermal initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide and di-tert-butyl peroxide; The photoinitiator is selected from at least one of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), 1-hydroxycyclohexylphenyl ketone (Irgacure 184), 2-hydroxy-2-methyl-1-phenyl-1-propanone (Irgacure 1173), and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (Irgacure 2959).
[0041] Specifically, both the thermal initiator and the photoinitiator mentioned above can initiate free radical polymerization of polymerizable carbon-carbon double bonds. The thermal initiation system is suitable for overall in-situ curing after battery encapsulation, with a simple process and is conducive to uniform gel formation inside the cell; the photoinitiation system has a fast curing speed and is suitable for the rapid preparation of thin-film electrolytes or transparent photocell structures.
[0042] Furthermore, controlling the initiator dosage to 0.2wt%-0.5wt% of the combined mass of the vinylsiloxy phosphate derivative and the silicon double bond polymerizable monomer can reduce the adverse effects of excessive initiator residue on electrolyte oxidative stability, interfacial side reactions, and cycle performance while ensuring polymerization conversion and gelation speed.
[0043] A second aspect of the present invention provides a method for preparing the above-described all-silicon-containing flame-retardant crosslinked gel electrolyte, comprising: Dehydration treatment of organosilane solvents, lithium salts, functional additives, vinylsiloxy phosphate derivatives and silicon double bond polymerizable monomers is carried out under an inert atmosphere. Lithium salts and functional additives are dissolved in an organosilane solvent to obtain a silicon-based electrolyte; Add a vinylsiloxy phosphate derivative, a silicon double bond polymerizable monomer, and an initiator to a silicon-based electrolyte, mix thoroughly, and obtain a gel electrolyte precursor solution. The precursor solution of the gel electrolyte is subjected to thermally initiated polymerization or photoinitiated polymerization to obtain a fully silicon-containing flame-retardant crosslinked gel electrolyte.
[0044] Optionally, the water removal treatment may include molecular sieve drying, vacuum drying, vacuum distillation, filtration to remove impurities, or neutral alumina short column treatment; the water content of the silicon-based electrolyte, phosphate derivatives containing vinylsiloxy groups, and polymerizable monomers containing silicon double bonds shall be less than 20 ppm, preferably less than 10 ppm.
[0045] Optionally, the temperature for thermally initiated polymerization is 40℃-90℃, and the time is 0.5h-12h.
[0046] Optionally, the photoinitiated polymerization reaction is carried out by irradiation with ultraviolet light or visible light with a wavelength of 365nm-405nm for 1min-60min.
[0047] This invention provides a method for preparing a fully silicon-containing flame-retardant crosslinked gel electrolyte. First, the silicon-based electrolyte components and polymerizable monomers are dehydrated. Then, a precursor solution is prepared under an inert atmosphere. This method helps reduce byproducts caused by the reaction of organosilane solvents, lithium salts, and silicon-containing monomers with water, thus lowering the risk of interfacial side reactions. Injecting the precursor solution into the battery followed by thermally or photo-initiated in-situ polymerization allows the gel network to form directly within the pores of the electrodes and separator, thereby improving electrode / electrolyte contact, reducing the risk of electrolyte leakage and phase separation, and enhancing the adaptability of battery assembly processes.
[0048] A third aspect of the present invention provides a lithium battery, comprising a positive electrode, a negative electrode, a separator, and the aforementioned all-silicon flame-retardant crosslinked gel electrolyte; wherein the positive electrode active material is selected from LiCoO2 and LiNi. x Co Mn 1-x- O2, LiNi x Co Al 1-x- At least one of O2, LiNi0.8Co0.1Mn0.1O2, LiNi0.6Co0.2Mn0.2O2, LiFePO4, LiMn2O4, and LiNi0.5Mn1.5O4; the negative electrode is selected from one of lithium metal negative electrode, graphite negative electrode, silicon-carbon negative electrode, hard carbon negative electrode, and lithium titanate negative electrode.
[0049] In a fourth aspect of the present invention, the fully silicon-containing flame-retardant crosslinked gel electrolyte is suitable for various electrochemical energy storage devices, including but not limited to lithium-ion batteries, lithium metal batteries, and battery systems with special performance requirements such as high-voltage batteries, wide-temperature batteries, and high-safety energy storage devices.
[0050] In summary, the embodiments of this invention utilize phosphate ester derivatives containing vinylsiloxy groups as silicon-containing flame-retardant crosslinking agents, and synergistically construct a gel network with silicon-containing polymerizable double-bonded organic monomer derivatives and silicon-based electrolytes. This fixes the flame-retardant structural units within the gel framework, reducing the risk of migration and loss of flame-retardant components. The resulting gel electrolyte effectively immobilizes the silicon-based electrolyte, reducing electrolyte leakage and combustion risks, and improving the electrolyte's flame-retardant performance, thermal stability, and morphological stability. The resulting gel electrolyte exhibits good ion conductivity and interfacial wettability, which helps improve electrode / electrolyte interface contact, enhancing battery cycle stability and safety performance. In conclusion, the fully silicon-containing flame-retardant crosslinked gel electrolyte provided by this invention combines flame retardancy, thermal stability, gel formation stability, and electrochemical performance, making it suitable for high-safety lithium battery systems.
[0051] The present invention will be described in detail below through examples. Unless otherwise specified, the instruments, pharmaceuticals, and reagents used in the following examples are all commercially available products. In the following examples, the ratio of vinylsiloxy phosphate derivatives to silicon double-bond polymerizable monomers is based on the molar ratio of the polymerizable carbon-carbon double bonds contained in the two components.
[0052] Phosphate derivatives containing vinylsiloxy groups: Tris(vinyl dimethyl silyl) phosphate, abbreviated as TVDMSP: purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd., CAS number 113419-25-3.
[0053] Organosilane solvents: Methyltrimethoxysilane, abbreviated as MTMS: purchased from Sigma-Aldrich, CAS number 1185-55-3; Methoxytrimethylsilane, abbreviated as METMS: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number 1825-61-2; Methyltris(trimethylsiloxy)silane, abbreviated as TTMS: purchased from Shanghai McLean Biochemical Technology Co., Ltd., CAS No. 17928-28-8.
[0054] Polymerizable organic monomer derivatives containing silicon double bonds: Bis[3-(methacryloyloxy)propyl]tetramethyldisiloxane: available from Shanghai Maclean Biochemical Technology Co., Ltd. or equivalent commercial sources, CAS No. 18387-19-4; 3-[tris(trimethylsiloxy)silyl]propyl methacrylate: available from Shanghai Aladdin Biochemical Technology Co., Ltd. or equivalent commercial sources, CAS No. 17096-07-0; Methyl methacrylate [dimethoxy(methyl)silyl]: purchased from Shanghai Maclean Biochemical Technology Co., Ltd., CAS No. 121177-93-3; 3-Methacryloxypropyltrimethoxysilane (KH570): Available from Shanghai Aladdin Biochemical Technology Co., Ltd. or equivalent commercial sources, CAS No. 2530-85-0; Methacryloxypropyltriethoxysilane: available from Shanghai McLean Biochemical Technology Co., Ltd. or equivalent commercial sources, CAS No. 21142-29-0.
[0055] Silicon-free comparative monomers: Butyl acrylate, abbreviated as BA: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number 141-32-2; 2-Cyanoethyl methacrylate: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 4513-53-5.
[0056] The aforementioned organic monomer derivatives containing silicon-polymerizable double bonds all contain polymerizable carbon-carbon double bonds and can undergo free radical copolymerization or cross-linking reactions with phosphate ester derivatives containing vinylsiloxy groups under the action of initiators, thereby participating in gel network formation. Butyl acrylate and 2-cyanoethyl methacrylate are silicon-free comparative monomers and are only used in the comparative examples to illustrate the role of silicon-polymerizable monomers containing double bonds.
[0057] Lithium salts: Lithium difluorosulfonylimide, abbreviated as LiFSI: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 171611-11-3; Lithium bis(trifluoromethanesulfonyl)imide, abbreviated as LiTFSI: purchased from Shanghai Maclean Biochemical Technology Co., Ltd., CAS No. 90076-65-6; Lithium hexafluorophosphate, abbreviated as LiPF6: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number 21324-40-3.
[0058] Functional additives: Ethylene carbonate, abbreviated as VC: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 872-36-6.
[0059] Initiator: Azobisisobutyronitrile (AIBN): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No. 78-67-1.
[0060] Conventional carbonate electrolyte (used in the comparative example): 1 mol / L LiPF6 was dissolved in a mixed solvent of EC / DEC, wherein the volume ratio of EC to DEC was 1:1.
[0061] In the following examples, room temperature refers to a temperature of 23±2℃.
[0062] Preparation examples and embodiments The following preparation examples, embodiments, and comparative examples are used to further illustrate the present invention, but should not be construed as limiting the scope of protection of the present invention.
[0063] Preparation Example 1: Preparation of METMS Silicon-based Electrolyte In an argon glove box with a water and oxygen content of less than 1 ppm, the dehydrated METMS was added to a glass bottle, and LiFSI, lithium difluorooxalate borate and vinylene carbonate were added in sequence. The mixture was stirred until completely dissolved to obtain the METMS silicon-based electrolyte.
[0064] The METMS silicon-based electrolyte comprises, by weight, 79.1 parts METMS, 18.4 parts LiFSI, 0.5 parts lithium difluorooxalate borate, and 2.0 parts vinylene carbonate.
[0065] Preparation Example 2: Preparation of MTMS-METMS Composite Silicon-Based Electrolyte In an argon-filled glove box with a water and oxygen content below 1 ppm, MTMS and METMS, after being dehydrated by molecular sieve treatment, were added to a glass bottle and stirred until homogeneous to obtain a siloxane mixed solvent. LiFSI, lithium difluorooxalate borate, and vinylene carbonate were then added, and stirring continued until the lithium salt was completely dissolved to obtain the MTMS silicon-based electrolyte.
[0066] The MTMS silicon-based electrolyte comprises, by weight, 77.5 parts MTMS, 7.0 parts METMS, 20.0 parts LiFSI, 0.5 parts lithium difluorooxalate borate, and 2.0 parts vinylene carbonate.
[0067] Preparation Example 3: Preparation of TTMS Silicon-based Electrolyte In an argon glove box with a water and oxygen content of less than 1 ppm, TTMS after dehydration treatment was added to a glass bottle, followed by the addition of lithium salt, lithium difluorooxalate borate, and vinylene carbonate. The mixture was stirred continuously until completely dissolved to obtain a TTMS silicon-based electrolyte.
[0068] The TTMS silicon-based electrolyte comprises, by weight, 75.0 parts TTMS, 22.0 parts LiFSI, 1.0 part lithium difluorooxalate borate, and 2.0 parts vinylene carbonate.
[0069] Preparation Example 4: Preparation of METMS-LiTFSI Silicon-based Electrolyte In an argon glove box with a water and oxygen content of less than 1 ppm, METMS, which has been dehydrated by molecular sieve treatment, is added to a glass bottle. LiTFSI, lithium difluorooxalate borate, and vinylene carbonate are then added, and the mixture is stirred continuously until the lithium salt is completely dissolved to obtain METMS-LiTFSI silicon-based electrolyte.
[0070] The METMS-LiTFSI silicon-based electrolyte comprises, by weight: 79.1 parts METMS, 18.4 parts LiTFSI, 0.5 parts lithium difluorooxalate borate, and 2.0 parts vinylene carbonate.
[0071] Example 1 At room temperature, in an argon glove box, the METMS silicon-based electrolyte obtained in Preparation Example 1, tris(vinyl dimethyl silyl) phosphate, methyl methacrylate [dimethoxy(methyl)silyl] methyl methacrylate and AIBN were added to a mixing container and magnetically stirred for 30 min to obtain a gel electrolyte precursor solution.
[0072] Tris(vinyldimethylsilyl)phosphate is used as a phosphorus- and silicon-containing flame-retardant crosslinking component; methyl methacrylate (dimethoxy(methyl)silyl) is used as a silicon-containing polymerizable monomer; and azobisisobutyronitrile (AIBN) is used as the initiator. If the methyl methacrylate (dimethoxy(methyl)silyl) contains BHT stabilizer, it is treated with a neutral alumina short column before solution preparation.
[0073] Based on a total mass of 100wt% for the gel electrolyte precursor solution, the content of tris(vinyldimethylsilyl)phosphate is 3wt%; the molar ratio of the polymerizable carbon-carbon double bond in tris(vinyldimethylsilyl)phosphate to the molar ratio of the polymerizable carbon-carbon double bond in methyl methacrylate [dimethoxy(methyl)silyl] is 1:1.0; the amount of AIBN is 0.5wt% of the sum of the masses of the two polymerizable components, and the balance is METMS silicone electrolyte.
[0074] The obtained gel electrolyte precursor solution was injected into an NCM811 / Li battery, encapsulated, and heated at 60°C for 3 hours to allow in-situ polymerization inside the battery, resulting in a fully silicon-containing flame-retardant crosslinked gel electrolyte battery, denoted as GPE-1. Example 1 serves as a representative example of the infrared spectral characterization of this invention.
[0075] Example 2 The difference from Example 1 is that the polymerizable monomer containing silicon double bonds is replaced by methyl methacrylate [dimethoxy(methyl)silyl] ester with bis[3-(methacryloyloxy)propyl]tetramethyldisiloxane, while the other conditions are the same, and it is referred to as GPE-2.
[0076] Example 3 The difference from Example 1 is that the polymerizable monomer containing silicon double bonds is replaced by methyl methacrylate [dimethoxy(methyl)silyl] methacrylate with 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, while the other conditions are the same, and it is referred to as GPE-3.
[0077] Example 4 The difference from Example 1 is that the polymerizable monomer containing silicon double bonds is replaced by methyl methacrylate [dimethoxy(methyl)silyl] methacrylate with 3-methacryloyloxypropyltrimethoxysilane, while the other conditions are the same. This is referred to as GPE-4.
[0078] Example 5 The difference from Example 1 is that the polymerizable monomer containing silicon double bonds is replaced by methyl methacrylate [dimethoxy(methyl)silyl] methyl methacrylate with methacryloyloxypropyltriethoxysilane, while the other conditions are the same. This is referred to as GPE-5.
[0079] Example 6 The difference from Example 2 is that the silicon-based electrolyte used is the MTMS-METMS compound silicon-based electrolyte obtained in Preparation Example 2, and the other conditions are the same, which is referred to as GPE-6.
[0080] Example 7 The difference from Example 2 is that the silicon-based electrolyte used is the TTMS silicon-based electrolyte obtained in Preparation Example 3, and the other conditions are the same, denoted as GPE-7.
[0081] Example 8 The difference from Example 2 is that the silicon-based electrolyte used is the METMS-LiTFSI silicon-based electrolyte obtained in Preparation Example 4, and the other conditions are the same, denoted as GPE-8.
[0082] Table 1 Formulation Design of Examples
[0083] Total mass of vinylsiloxy phosphate derivatives and silicon double bond polymerizable monomers. Note: In Examples 1 to 8, the amount of tris(vinyldimethylsilyl)phosphate was 3 wt% of the total mass of the gel electrolyte precursor solution; the molar ratio of the polymerizable carbon-carbon double bond in tris(vinyldimethylsilyl)phosphate to the molar ratio of the polymerizable carbon-carbon double bond in the silicon double bond polymerizable monomer was 1:1.0; the amount of AIBN was 0.5 wt% of the sum of the masses of the two polymerizable components.
[0084] Comparative Example 1 The difference from Example 1 is that the METMS silicon-based electrolyte is replaced with a conventional carbonate liquid electrolyte (1 mol / L LiPF6 dissolved in an EC / DEC mixed solvent, wherein the volume ratio of EC to DEC is 1:1), and no vinylsiloxy phosphate derivatives, no polymerizable monomers containing silicon double bonds are added, and no in-situ polymerization reaction is carried out. This is referred to as D-GPE-1.
[0085] This comparative example is used as a control for conventional liquid electrolytes.
[0086] Comparative Example 2 The difference from Example 1 is that no vinylsiloxy phosphate derivative is added; only methyl methacrylate [dimethoxy(methyl)silyl] and an initiator are added, while the other conditions remain the same. This is referred to as D-GPE-2.
[0087] This comparative example illustrates the effect of vinylsiloxy phosphate derivatives on flame retardant properties, crosslinking density, and gel stability.
[0088] Comparative Example 3 The difference from Example 1 is that no polymerizable monomer containing silicon double bonds is added; only a phosphate derivative containing vinylsiloxy groups and an initiator are added, while the other conditions remain the same. This is referred to as D-GPE-3.
[0089] This comparative example illustrates the effect of silicon-containing double-bonded polymerizable monomers on the formation of flexible gel networks, interfacial wetting, and electrochemical performance.
[0090] Comparative Example 4 The difference from Example 1 is that methyl methacrylate [dimethoxy(methyl)silyl] ester in Example 1 is replaced with butyl acrylate (BA) without silicon, while the other conditions are the same. This is referred to as D-GPE-4.
[0091] This comparative example illustrates that ordinary flexible acrylate monomers cannot replace the role of silicon-containing flexible segments in flame retardancy and interface stability.
[0092] Comparative Example 5 The difference from Example 1 is that methyl methacrylate [dimethoxy(methyl)silyl] ester in Example 1 is replaced with 2-cyanoethyl methacrylate without silicon, while the other conditions are the same, and it is referred to as D-GPE-5.
[0093] This comparative example illustrates that even with the introduction of a polar cyano monomer, the flame retardancy, thermal stability, and high-voltage interface stability of the system remain insufficient in the absence of a silicon-oxygen structure.
[0094] Comparative Example 6 The difference from Example 1 is that LiFSI in the METMS silicon-based electrolyte is replaced with LiPF6, while the other conditions remain the same, and it is referred to as D-GPE-6.
[0095] This comparative example illustrates the effect of lithium salt type on the interfacial stability and cycling performance of METMS silicon-containing flame-retardant gel electrolyte.
[0096] Table 2 Comparative Design
[0097] Test case The electrolytes obtained in Examples 1-8 and Comparative Examples 1-5 were used to assemble NCM811 / Li batteries. The battery test voltage range was 3.0V-4.3V. The first three cycles were activated at 0.1C, followed by cycling tests at 0.5C. The test temperature was 25℃.
[0098] Meanwhile, the resulting electrolyte was tested for gelation properties, gel content, flame retardancy, ionic conductivity, electrochemical stability window, and Li / Li symmetric cell performance.
[0099] Fourier transform infrared (FTIR) spectroscopy was performed on the polymerization precursor solutions and post-polymerization samples of Example 1 (GPE-1) and Comparative Example 4 (D-GPE-4). The measurements were conducted in ATR mode with a scan range of 4000 cm⁻¹. -1 -400 cm -1 The resolution is 4 cm. -1 The number of scans shall not be less than 32; by comparing the changes of C=C related absorption peaks before and after polymerization, the transformation of polymerizable double bonds shall be determined, and the C=O, Si-O and PO-Si related absorption peaks shall be used as auxiliary evidence for structural retention and the presence of silicon- and phosphorus-containing components.
[0100] Preferably, the focus is on comparing approximately 1630 cm. -1 -1640 cm -1 Nearby C=C stretching vibration absorption and approximately 810 cm -1 -990 cm -1 The variation of double bond out-of-plane vibrational absorption within the range; the specific peak position is based on the measured spectrum.
[0101] Table 3. Results of Gel and Flame Retardant Properties Tests
[0102] Table 4 Cyclic performance test results of NCM811 / Li batteries
[0103] Results Analysis From Tables 3 and 4 and Figure 1 It can be seen that all of Examples 1 to 8 can form stable cross-linked gel electrolytes and exhibit good flame retardant properties, ion transport properties and electrochemical stability.
[0104] Generally, the all-silicon-containing flame-retardant crosslinked gel electrolyte provided by this invention has a gel content of 84.8%–90.6%, a self-extinguishing time of 0 s–1 s, and an ionic conductivity of 0.98 mS·cm at 25 °C. - ¹~1.20 mS·cm - ¹, the electrochemical stability window is 4.63 V to 4.78 V; when used in NCM811 / Li batteries, the capacity retention after 250 cycles at 0.5C is 81.5% to 87.0%, the average coulombic efficiency is 99.1% to 99.6%, and the stable cycling time of Li / Li symmetric cells is 520 h to 700 h.
[0105] Preferably, the all-silicon-containing flame-retardant crosslinked gel electrolyte provided by the present invention has a gel content of 84.8%–90.6%, a self-extinguishing time of 0 s–1 s, and an ionic conductivity of 1.10 mS·cm at 25 °C. - ¹~1.18 mS·cm - ¹, the electrochemical stability window is 4.64 V to 4.78 V; when used in NCM811 / Li batteries, the capacity retention after 250 cycles at 0.5C is 86.0% to 87.0%, the average coulombic efficiency is 99.5% to 99.6%, and the stable cycling time of Li / Li symmetric cells is 670 h to 700 h.
[0106] Among them, Example 1, constructed with METMS silicon-based electrolyte, LiFSI lithium salt, tris(vinyldimethylsilyl)phosphate, and methyl methacrylate [dimethoxy(methyl)silyl]methyl methacrylate, exhibited the best overall performance as a fully silicon-containing flame-retardant crosslinked gel electrolyte (GPE-1). Its gel content reached 90.6%, its self-extinguishing time was 0 s, and its ionic conductivity reached 1.18 mS·cm. -1The electrochemical stability window reaches 4.78 V; in the NCM811 / Li battery test, GPE-1 showed high cycle stability, with a capacity retention of 87.0% after 250 cycles, and a stable cycle time of 700 h for Li / Li symmetric batteries, indicating that the system can balance flame retardant safety and long-term electrochemical stability.
[0107] Example 2 uses bis[3-(methacryloyloxy)propyl]tetramethyldisiloxane as a polymerizable monomer containing silicon double bonds. The resulting GPE-2 also has good flame retardant properties, thermal stability and interface stability. The capacity retention rate after 250 cycles reaches 86.0%, and the stable cycle time of the Li / Li symmetric battery reaches 670 h. The overall performance is slightly lower than that of GPE-1, so it is the second preferred embodiment of the present invention.
[0108] Compared with Example 1, Comparative Example 1 uses a conventional carbonate liquid electrolyte. Due to the lack of an in-situ cross-linked gel network structure, it cannot achieve effective flame retardant protection and exhibits continuous combustion. At the same time, due to the more obvious side reactions at the interface between the liquid electrolyte and the high-nickel cathode, its cycle stability is significantly reduced. This indicates that constructing a gel network structure plays an important role in improving battery safety and cycle performance.
[0109] In Comparative Example 2, no phosphate derivative containing vinylsiloxy groups was added. Although the resulting gel could form a certain cross-linked structure, the gel content, self-extinguishing properties, and electrochemical stability all decreased. This indicates that the phosphate derivative containing silicon not only participates in the cross-linking reaction, but also improves the gel network performance by utilizing the flame-retardant effect of phosphorus and the stabilizing effect of silicon-oxygen structure.
[0110] In Comparative Example 3, no polymerizable monomers containing silicon double bonds were added, resulting in a decrease in gel network integrity, leading to a reduction in gel content and a deterioration in interfacial stability. This indicates that the participation of monomers containing silicon double bonds in free radical copolymerization helps to construct a more stable three-dimensional cross-linked structure and improves the compatibility of the electrolyte-electrode interface.
[0111] Comparative Example 4 uses butyl acrylate (BA) instead of the polymerizable monomer containing silicon double bonds. Although BA can participate in free radical polymerization to form a gel structure, it is weaker than Example 1 in terms of thermal stability, flame retardancy and interface protection due to the lack of silicon-oxygen segments. This results in a decrease in battery cycle retention rate and stable cycle time of Li / Li symmetric battery, indicating that the silicon-containing structure plays a key role in improving the overall performance of gel electrolyte.
[0112] Comparative Example 5 uses 2-cyanoethyl methacrylate to replace the polymerizable monomer containing silicon double bonds. The cyano structure has strong polarity and can promote lithium salt dissociation and ion migration to a certain extent. However, due to the lack of silicon-oxygen structure, it cannot form an effective silicon-oxygen stable network. Therefore, its flame retardant performance and long-term cycle stability are still lower than those of GPE-1.
[0113] In Comparative Example 6, LiPF6 was used instead of LiFSI as the lithium salt. The ion transport performance, electrochemical stability window, and cycling performance of the resulting gel electrolyte all decreased. This indicates that LiFSI lithium salt has better compatibility with the METMS silicon-containing electrolyte system, which is beneficial to improving the high voltage stability and long-term cycling performance of the gel electrolyte.
[0114] Depend on Figure 2 It can be seen that the TVDMSP monomer and the BA monomer are at approximately 1630 cm⁻¹ -1 ~1640 cm -1 Absorption peaks for the C=C stretching vibration of polymerizable carbon-carbon double bonds are present at all locations, with a peak at approximately 810 cm⁻¹. -1 ~990 cm -1 The absorption exhibits characteristic absorption related to the out-of-plane vibration of the CH terminal group of the double bond within the range. After thermally initiated polymerization, the above-mentioned C=C related absorption peaks in the comparative gel (Comparative Example 4) and the experimental gel (Example 1) were significantly weakened or basically disappeared, indicating that the polymerizable carbon-carbon double bonds in the monomer have undergone free radical polymerization and formed the corresponding gel network.
[0115] Meanwhile, the characteristic absorption of the ester group C=O in the BA structure can still be observed in the comparative gel (Comparative Example 4), indicating that the acrylate structure is retained after polymerization; the experimental gel (Example 1) at approximately 1000 cm⁻¹ -1 The presence of Si-O and PO-Si related absorption bands nearby indicates that the silicon and phosphorus-containing structural units in TVDMSP and the silicon-containing double-bond polymerizable monomers were not destroyed during polymerization and were fixed in the gel backbone. These results demonstrate that tris(vinyldimethylsilyl)phosphate can undergo free radical copolymerization with silicon-containing double-bond polymerizable monomers to successfully construct a phosphorus- and silicon-containing three-dimensional cross-linked gel network, providing a structural basis for the flame-retardant properties, thermal stability, and interfacial stability of the resulting gel electrolyte.
[0116] The results above demonstrate that the fully silicon-containing flame-retardant crosslinked gel electrolyte provided by this invention can form a stable three-dimensional crosslinked network in situ inside the battery, effectively fixing the silicon-based electrolyte and reducing the risk of electrolyte leakage and migration of active components. The vinylsiloxy phosphate derivative contains PO-Si bonds and polymerizable carbon-carbon double bonds, which can participate in the construction of the gel network as a silicon-containing flame-retardant crosslinking agent, ensuring the stable existence of phosphorus-containing silicon-containing flame-retardant structural units within the polymer backbone. This provides flame-retardant inhibition at high temperatures or in the early stages of thermal runaway, reducing the risk of flammable component volatilization and combustion diffusion.
[0117] The fully silicon-containing flame-retardant crosslinked gel electrolyte provided by this invention maintains good ion conductivity while also exhibiting high thermal stability, flame retardancy, and interfacial stability. The synergistic effect of the silicon-based electrolyte and the crosslinked gel network not only improves the wettability of the electrolyte to the electrodes and separator but also mitigates side reactions at the electrode / electrolyte interface, promoting the formation of a stable interfacial film, thereby improving lithium deposition / stripping reversibility and battery cycle life. Compared with conventional liquid electrolytes or gel systems without silicon-containing flame-retardant crosslinking agents, the gel electrolyte obtained by this invention exhibits better gelation stability, flame retardant properties, and electrochemical stability.
[0118] In summary, this invention achieves a unified approach to flame-retardant structure immobilization, liquid component gelation, and continuous ion transport through the synergistic design of "phosphite derivatives containing vinylsiloxy groups, organic monomer derivatives containing silicon polymerizable double bonds, and silicon-based electrolytes." This provides an effective technical solution for developing lithium-ion and lithium metal batteries that combine high safety, high ionic conductivity, and long cycle life.
[0119] It will be readily understood by those skilled in the art that the above-described advantageous methods can be freely combined and superimposed without conflict. The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application. The above are merely preferred embodiments of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of this application, and these improvements and modifications should also be considered within the protection scope of this application.
Claims
1. A fully silicon-containing flame-retardant crosslinked gel electrolyte, characterized in that, The fully silicon-containing flame-retardant crosslinked gel electrolyte is obtained through in-situ polymerization of a gel electrolyte precursor solution composed of a silicon-based electrolyte, a phosphate ester derivative containing vinylsiloxy groups, a polymerizable monomer containing silicon double bonds, and an initiator; wherein... The silicon-based electrolyte includes an organosilane solvent, a lithium salt, and functional additives; The phosphate ester derivative containing vinylsiloxy groups contains PO-Si bonds and polymerizable carbon-carbon double bonds in its molecule, and the phosphate ester derivative containing vinylsiloxy groups is tris(vinyldimethylsilyl)phosphate. The polymerizable monomer containing silicon double bonds contains Si-O bonds and / or Si-C bonds in its molecule, and contains polymerizable carbon-carbon double bonds. The polymerizable monomer containing silicon double bonds is selected from one or more of the following: [dimethoxy(methyl)silyl]methyl methacrylate, bis[3-(methacryloyloxy)propyl]tetramethyldisiloxane, 3-methacryloyloxypropyltrimethoxysilane, methacryloyloxypropyltriethoxysilane, acryloyloxytriisopropylsilane, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, and octavinyl POSS. The phosphate derivative containing vinylsiloxy groups can undergo free radical copolymerization with the polymerizable monomer containing silicon double bonds; Based on a total mass of 100wt% for the gel electrolyte precursor solution, the mass of the vinylsiloxy phosphate derivative is 2wt%-8wt%, and the molar ratio of the polymerizable carbon-carbon double bond in the vinylsiloxy phosphate derivative and the polymerizable monomer containing silicon double bonds is 1:(0.3-2).
2. The all-silicon flame-retardant crosslinked gel electrolyte according to claim 1, characterized in that, The silicon-based electrolyte contains, by weight: 65-90 parts organosilane solvent, 10-30 parts lithium salt, and 2-8 parts functional additives.
3. The all-silicon flame-retardant crosslinked gel electrolyte according to claim 2, characterized in that: In the silicon-based electrolyte The organosilane solvent is selected from one or more of methyltrimethoxysilane, methoxytrimethylsilane, and methyltris(trimethylsiloxy)silane; The lithium salt is LiFSI and / or LiTFSI; The functional additive is selected from one or more of lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorophosphate, vinylene carbonate, fluoroethylene carbonate, and lithium nitrate.
4. The all-silicon flame-retardant crosslinked gel electrolyte according to claim 1, characterized in that: The initiator is selected from thermal initiators or photoinitiators, and the amount of the initiator is 0.2wt% to 0.5wt% of the combined mass of the vinylsiloxy phosphate derivative and the silicon double-bond polymerizable monomer; wherein, The thermal initiator is selected from at least one of azobisisobutyronitrile, benzoyl peroxide and di-tert-butyl peroxide; The photoinitiator is selected from at least one of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
5. The method for preparing the fully silicon-containing flame-retardant crosslinked gel electrolyte according to any one of claims 1-4, characterized in that, include: The silicon-based electrolyte, the vinylsiloxy phosphate derivative, the silicon double bond polymerizable monomer, and the initiator are mixed evenly to obtain a gel electrolyte precursor solution. The gel electrolyte precursor solution is subjected to thermally initiated polymerization or photoinitiated polymerization to obtain the fully silicon-containing flame-retardant crosslinked gel electrolyte.
6. The preparation method according to claim 5, characterized in that: The temperature for the thermally initiated polymerization reaction is 40℃-90℃, and the time is 0.5h-12h. The photoinitiated polymerization reaction is carried out by irradiation with ultraviolet or visible light with a wavelength of 365nm-405nm for 1min-60min.
7. A lithium battery, characterized in that: The lithium battery comprises a positive electrode, a negative electrode, a separator, and a fully silicon-containing flame-retardant crosslinked gel electrolyte as described in any one of claims 1-4; wherein the positive electrode active material is selected from LiCoO2 and LiNi. x Co Mn 1-x- O2, LiNi x Co Al 1-x- At least one of O2, LiNi0.8Co0.1Mn0.1O2, LiNi0.6Co0.2Mn0.2O2, LiFePO4, LiMn2O4, and LiNi0.5Mn1.5O4; the negative electrode is selected from one of lithium metal negative electrode, graphite negative electrode, silicon-carbon negative electrode, hard carbon negative electrode, and lithium titanate negative electrode.
8. The application of the fully silicon-containing flame-retardant crosslinked gel electrolyte according to any one of claims 1-4 in lithium-ion batteries or lithium metal batteries.
Citation Information
Patent Citations
Three-dimensional network flame-retardant silica gel electrolyte, preparation method thereof and preparation method of gel lithium ion battery
CN111326790A
Phosphorus-based cross-linking agent containing silyl ether, gel-state polymer electrolyte, solid-state pole piece and lithium ion battery
CN121270601A